Challenges for the Measurement of Innovation Ecosystems and Entrepreneurial Ecosystems in Brazil - Lèbre La Rovere, Renata; de Oliveira Santos, Guilherme; Louzada Xavier Vasconcellos, Bianca (REGEPE Entrepreneurship and Small Business Journal, 2020)
Purpose: This paper aims to identify metrics and indicators of innovation ecosystems and entrepreneurial ecosystems and to discuss the limitations of these metrics in the Brazilian case. Theoretical framework: From a theoretical point of view, the paper contributes to the analysis of the differences and similarities between the concepts of innovation ecosystems and entrepreneurial ecosystems. From a methodological perspective, the paper proposes indicators and metrics and points out the limitations for measuring entrepreneurial and innovative ecosystems in Brazil. Design/methodology/approach: The study’s qualitative approach is based on a literature review, a documentary research, and data collection for the characterization of innovation ecosystems and entrepreneurial ecosystems. The paper identifies the main indicators and metrics, their data sources and the limitations of these indicators and metrics in the Brazilian case. Findings: It was observed that despite the existence of multiple data sources, the measurement of entrepreneurial ecosystems in Brazil entails constraints such as time lag of the data; voluntary filling of databases; lack of transparency at the regional level; and incomplete or skewed data. Research, Practical & Social implications: From a theoretical point of view, the paper contributes to the analysis of the differences and similarities between the concepts of innovation ecosystems and entrepreneurial ecosystems. From a methodological point of view, the study proposes indicators and metrics and points out the limitations for the measurement of entrepreneurial and innovative ecosystems in Brazil. Originality/value: When identifying limitations, the paper proposes alternatives to improve the measurement of innovation ecosystems and entrepreneurial ecosystems in the country and in its different regions. This is essential for designing and monitoring public policies to support innovation, especially those aimed to support entrepreneurs and small businesses. JEL CODE: O30, L26 <!– End Crossmark Snippet –>